How to start knitting : all the tips, tricks, and techniques new knitters need to know - Lam, Brenda (Knitter) (Search Press, 2025)
So you want to learn how to knit? Enter your knitting era with self-taught knitwear designer Brenda Lam. From casting on to casting off, learn the fundamentals of knitting and then create 10 fun, chunky projects to wear with pride.